The Resistance Mechanisms of Lung Cancer Immunotherapy - Wang, Fen; Wang, Shubin; Zhou, Qing (Frontiers in Oncology, 2020)
Emerging immunotherapy has revolutionized lung cancer treatment in the past decade. By reactivating the host’s immune system, immunotherapy prolongs the survival period in some advanced lung cancer patients. However, resistance to immunotherapy is inevitable, which manifests as the lack of initial response or clinical benefit to therapy (primary resistance) or tumor progression after the initial period of clinical benefit (acquired resistance). Overcoming immunotherapy resistance is challenging owing to the complexly and dynamically interplay among malignancy cells and the defense system. This review aims to discuss the mechanisms that drive immunotherapy resistance and the innovative strategies implemented to overcome it in lung cancer.